The Effect of Risk Management on Direct and Indirect Capital Structure Deviations - Xiaoyi Li; Yung-Ming Shiu (Risks)
This study explores the effect of risk management on capital structure deviations. Specifically, we innovatively classify capital structure deviations into direct and indirect deviations, with our classification being based on deviations resulting mainly from changes in either actual or target leverage. Thus, if the variation in the actual leverage exceeds the variation in the target leverage, this deviation is considered direct. Conversely, if the target leverage varies more than the actual leverage, it is considered an indirect deviation. Our results reveal that risk management can help reduce these deviations, which mainly result from changes in actual leverage. We further demonstrate that insurers with direct deviations adjust their capital structure approximately 29.2% faster than insurers with indirect deviations.